The Consciousness Raising in Preserving of Miang Pa Pae Local Wisdom through the Participatory Learning Management Integration - Muenjaem, Samnao (Community and Social Development Journal, 2021)
The purposes of this research were 1) to construct a model for consciousness-raising of Miang local wisdom, and 2) to study the effect of using a model on Pa Pae Wittaya school student’s consciousness in preserving of Miang local wisdom. The population was 128 students. The research instruments were the document analysis form, the brainstorming guidelines, the participation behavior observation form, the observation form for teaching behavior of teachers, the Interview form for people in the community, the interview form for opinions, the student achievement score form, the quality assessment form of Miang local wisdom manual, the consciousness measure in conserving Miang local wisdom. The quantitative data were analyzed by percentage, mean, and standard deviation. The qualitative data were analyzed by content analysis. The research findings were summarized as follows: The model for consciousness-raising of Miang local wisdom included four components 1) principles 2) objective 3) the process and 4) the conditions. The model evaluation found that the model had the quality of its feasibility, usefulness, appropriateness, and validity at the highest level. The results of using a model on Pa Pae Wittaya school student’s achievement and consciousness in preserving Miang local wisdom. The average percentage of consciousness scores in preserving the local wisdom of all students passed the school criteria.